Mode of Action of Gabapentin in Chronic Neuropathic Pain Syndromes - Surges, Rainer; Feuerstein, Thomas J. (Arzneimittelforschung, 2002)
Gabapentin (GBP, CAS 60142-96-3) has anticonvulsant and antinociceptive properties; the latter relate especially to chronic neuropathic pain. The mode of action of GBP, possibly different in epilepsy and chronic pain syndromes, is only poorly understood. This minireview s aimed at compiling the different mechanisms by which GBP may diminish the nociceptive transmission in the dorsal horn of the spinal cord.
Keywords: Antinociception; CAS 60142-96-3; Gabapentin, pharmacodynamics; Neuropathie pain